The timing of interventions in early life and long-term consequences: The example of gestational diabetes. (August 2020) - Painter, Rebecca C.; Finken, Martijn J.J.; van Rijn, Bas B.
Abstract: The incidence of gestational diabetes mellitus (GDM) has seen a rapid global increase in the past decades. This could be attributed to the obesity pandemic and maternal age, as well as to alterations in clinical definitions. While GDM can immediately impact perinatal outcomes, it importantly heralds life-long and sizably increased risk of cardiometabolic disease for the child, including impaired glucose tolerance, obesity, increased risks of cardiovascular and renal disease, and poorer neurodevelopmental outcomes. It has been speculated by many that prevention of GDM and treatment of GDM could amend later life health consequences of offspring. Here, we provide a narrative review of such interventions aimed at preventing these sequelae and discuss their relative efficacy when applied during preconception, pregnancy, or in early neonatal life.